Question Number 100151 by student work last updated on 25/Jun/20
$$\sqrt{\mathrm{lnx}}\:−\mathrm{ln}\sqrt{\mathrm{x}}\:=\mathrm{0}\:\:\:\:\:\:\mathrm{x}=? \\ $$
Commented by bobhans last updated on 25/Jun/20
$$\mathrm{set}\:\sqrt{\mathrm{ln}\left(\mathrm{x}\right)}\:=\:\mathrm{u} \\ $$$$\mathrm{u}−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{u}^{\mathrm{2}} \:=\mathrm{0}\:\Rightarrow\frac{\mathrm{1}}{\mathrm{2}}\mathrm{u}\left(\mathrm{2}−\mathrm{u}\right)=\mathrm{0} \\ $$$$\begin{cases}{\mathrm{u}=\mathrm{0}\:\Rightarrow\mathrm{ln}\left(\mathrm{x}\right)=\mathrm{0}\:,\:\mathrm{x}=\mathrm{1}}\\{\mathrm{u}=\mathrm{2}\:\Rightarrow\mathrm{ln}\left(\mathrm{x}\right)=\mathrm{4}\:,\:\mathrm{x}\:=\:\mathrm{e}^{\mathrm{4}} }\end{cases} \\ $$$$ \\ $$